SERVICE STANDARDS MANUAL - Mahboub, Ahmed; Bashar Saryrah, Dr.; Obeidat, Ayman (British Journal of Marketing Studies, 2014)
As for the continued and rapid increasing of Dubai as one of the world most targeted areas for businesses and investments, transportation has become one of the main challenges that face decision makers in Dubai. RTA thus was established to unify responsibilities previously spread between several governmental departments (Dubai Municipality and Police Department). Moreover, RTA adopted decentralization by establishing 8 separate agencies and sectors in order to achieve highest levels of flexibility. The “RTA Service Standards Manual” governs the entire portfolio of existing and news services offered by RTA. The Manual is considered imperative to unify and standardize the varied approaches that are taken today in service development and monitoring